Audit Keamanan Sistem Informasi Berdasarkan Standar ISO 27002 (Studi Kasus: PT. Aneka Jaya Baut Sejahtera) - Halim, Merliana; Tanuwijaya, Haryanto; Mastan, Ignatius Adrian (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2012)
PT.AJBS is a company that works in providing items/machinery for industrial purposes. PT.AJBS has many product lines Therefore, implementing a new and capable information system is a must. The new system need to have modules such as invetory, transaction, customer & supplier data and accounting journal. These modules need to be integratedto the new system, called Integrated Trading System. In addition, information security management is important because company's information is an important asset for the company. PT.AJBS need to audit their current information security system to find out the level of security PT.AJBS has. ISO 27002 is the standard that PT.AJBS has to be met when auditing. ISO 27002 standard is chosen because of its flexibility. It can be tailored according to the company's needs, company's visions, company's security system requirement, business processes, human resource needa and the structure of the organization, as well as information security system management. The result of maturity level 2.49 is produced from the implementation of information security system audit. The result is categorized to level 2, which is repeatable. This research also produces reccomendations for PT.AJBS such as better information system processes and improvement in level of information security Keywords: audit, information security, ISO 27002